Clean ethics for a dysfunctional age - Herman, Stewart W. (Word & world, 2016)
We need something like Luther's "estates" approach as a template for moral reasoning: identifying what functions are critical to sustain a resilient society, identifying where responsibilities for those functions already lie, and then reinforcing as he did the roles needed to carry them out.